Actual Sensing Sensitivity and SNR Measurement of Optical Tweezers Based on Coulomb Force Input - Jiaojiao Wang; Xingfan Chen; Shaochong Zhu; Zhenhai Fu; Nan Li; Huizhu Hu (Photonic Sensors, 2022)
Abstract Sensing sensitivity is the key performance of optical tweezers. By adjusting the frequency and magnitude of an applied Coulomb force as an input of optical tweezers, we directly measured the sensitivity and signal-to-noise ratio (SNR) of a system and indirectly calculated the actual noise magnitude. Combined with an output filter, the relationship between the SNR and bandwidths was studied. We established the simulation model of a system using Simulink and simulated the relationship between the SNR and magnitude of the input forces and filter bandwidths. In addition, we built an experimental system to determine the relationship between the SNR and the magnitude of the input forces and filter bandwidths. The actual minimum detectable force was measured as 1.8275×10−17 N at a 1 Hz bandwidth. The experimental results were correlated with the simulation and theoretical results, confirming the effectiveness of the proposed method and demonstrating the high sensitivity of vacuum optical tweezers as mechanical sensors. We proposed a novel method of calibration and measurement of system sensing parameters by applying an actual force that was more direct and precise than the theoretical calculation method that requires accurate fitting parameters, such as the particle radius and density. This method can be employed to analyze the system noise and phase characteristics to confirm and improve the real performance of the system.